Сопоставительный анализ лексики канадского, британского и американского английского - Любеев, В.С.; Кушпрак, Е.В.; Куксо, Д.А. (Культура народов Причерноморья, 2013)
Статья посвящена исследованию заимствований из американского и британского
варианта английского языка в канадский английский. Методом сплошной выборки были выявлены
заимствования американизмов и бритицизмов в сфере быта. В ходе анализа выборки, было выявлено,
что из 180 заимствованных лексических единиц в канадском английском, 99 – это заимствования из
британского английского, и 81 – из американского варианта английского языка. Дана тематическая
классификация и количественный анализ заимствований из американского и британского английского в
канадский английский.
Ключевые слова: канадский английский, заимствования, сопоставительный анализ. Ця стаття присвячена дослідженню запозичень з американського та британського варіанту
англійської мови до канадського англійського. Методом суцільної вибірки були виявлені запозичення
американізмів і бритицизмів у галузі побуту. У ході аналізу вибірки, було виявлено, що зі 180 запозичених
лексичних одиниць в канадському англійському 99 – це запозичення з британського англійського та 81 – з
американського варіанту англійської мови. Надана тематична класифікація та кількісний аналіз
запозичень з американського та британського англійського у канадський англійський.
Ключові слова: канадський англійський, запозичення, порівняльний аналіз. The article is dedicated to the research of the borrowings from American and British English to
Canadian English. By means of the method of continuous sampling, such borrowings as Americanisms and
Briticisms in the sphere of everyday life (food and drinks; clothes; furniture; transport; professions;
organizations; holidays; arts; political organizations; sociocultural events; establishments and others) were
found. During the analysis there were detected 180 borrowings in Canadian English, among which there are 99
borrowings from British English and 81 borrowings are from American variant of English. Thematic
classification and quantitative analysis of American and British variant of English is given in the article. The
research is worth of attention because it gives us an opportunity to see the way the language changes. One can
see how American English and British variant of English influence Canadian variant. Such researches are
always actual, because language is like a living organism; it can appear, change and die. That is why it is
necessary to pay attention to the changes that happen or may happen in any language, especially when we are
talking about international languages.
Key words: Canadian English, borrowings, comparative analysis.